Poster of the first Monterey Jazz Festival - Vinnie Lopez:::Photographer::::::::::::; Steven Domingo:::Photographer:::::::::::: (Monterey, California, 2023)
Photograph of the Poster of the first Monterey Jazz Festival,1958. This poster is found on exhibit in Ed Ricketts' Pacific Biological Laboratory, 800 Cannery Row in Monterey. The Monterey Jazz Festival is an annual music festival that takes place in Monterey, California, United States. It debuted on October 3, 1958, championed by Dave Brubeck and co-founded by jazz and popular music critic Ralph J. Gleason and jazz disc jockey Jimmy Lyons. It was in 1958 that Frank Wright, Ed Haber, Joe Turner, Fred Fry and Ed Larsh, purchased the building under the name "Pacific Biological Laboratories." They held weekly meetings for club members, many of whom were prominent Monterey artists and writers, and several club members helped to start the Monterey Jazz Festival.